Environmental audit, as the main tool for improving and protecting the environment (Journal of Economic Research & Business Administration, 2024)
Environmental concerns are getting more evident in the context of establishing commercial links. In particular, the nature users themselves, governmental institutions, and private and public organizations that exert control have the challenge of determining the extent of harm done to it and the likelihood of such damage.The primary goal of the study is to clarify how, while upholding the idea of sustainable development, the environmental audit helps to preserve and improve the environment. Because of this, one of the three worldwide strategies for determining and creating the environmental audit was applied.After reviewing the pertinent and readily available domestic and international literature, conclusions about the environmental audit's influence on environmental protection and improvement were reached. The findings of the research indicate a clear link between environmental audit requirements and environmental improvement as well as pollution. The research findings will be put into practice by developing precise suggestions to minimize pollution and increase environmental protection.The study’s significance stems from the authors’ definition of the prerequisites for the creation and formulation of an environmental audit for environmental improvement and protection purposes.Key words: environmental audit, losses of pollutants, air pollution, losses, environment.